The KαL¹, KαL², and KαL³ X-Ray Emission of Aluminium under Electron Impact - Al-Omari, M.A.M.; Borovyi, M.O. (Металлофизика и новейшие технологии, 2018)
The relative intensities, γ=I(KαL¹)/I(Kα₁,₂), η=I(KαL²)/KαL¹ and χ=I(KαL³)/I(KαL¹), of x-ray emission Kα₁,₂, KαL¹, KαL², and KαL³ lines’ groups of aluminium are experimentally studied under the excitation by electron impact in the range of accelerating voltages U= 4.5–100 kV. Относительные интенсивности γ=I(KαL¹)/I(Kα₁,₂)γ=I(KαL¹)/I(Kα₁,₂), η=I(KαL²)/I(KαL¹) и χ=I(KαL³)/I(KαL¹) групп рентгеновских эмиссионных линий Kα₁,₂, KαL¹, KαL² и KαL³ алюминия экспериментально исследованы при электронной бомбардировке в диапазоне ускоряющих напряжений U= 4,5–100 кВ. Відносні інтенсивності γ=I(KαL¹)/I(Kα₁,₂)γ=I(KαL¹)/I(Kα₁,₂), η=I(KαL²)/I(KαL¹) та χ=I(KαL³)/I(KαL¹) груп рентґенівських емісійних ліній Kα₁,₂, KαL¹, KαL² та KαL³ алюмінію експериментально досліджено при електронному бомбуванні у діяпазоні прискорювальних напруг U= 4,5–100 кВ.